2007
DOI: 10.1002/anie.200700608
|View full text |Cite
|
Sign up to set email alerts
|

The Preparation of Supported NiO and Co3O4 Nanoparticles by the Nitric Oxide Controlled Thermal Decomposition of Nitrates

Abstract: Metal (oxide) nanoparticles smaller than about 20 nm have received widespread interest recently because of their envisioned applications in electronics, optics, and magnetic storage devices.[1] They are currently used as catalysts for the production of fuels and chemicals and the reduction of environmental pollution.[2] High surface-to-volume ratios are important for these particles since catalytic processes take place at the metal (oxide) surface; therefore supports such as SiO 2 and Al 2 O 3 are generally us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
138
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 225 publications
(147 citation statements)
references
References 30 publications
(9 reference statements)
8
138
1
Order By: Relevance
“…This shows the beneficial impact of NC on the Co 3 O 4 crystallite size, which is in line with previous findings [5,6,31].…”
Section: Xrdsupporting
confidence: 93%
See 2 more Smart Citations
“…This shows the beneficial impact of NC on the Co 3 O 4 crystallite size, which is in line with previous findings [5,6,31].…”
Section: Xrdsupporting
confidence: 93%
“…[1][2][3][4] A recent example of improving the catalytic activity using this methodology is provided in a previous contribution from our laboratory, where a cobalt-on-silica catalyst was synthesized by an impregnation and drying step, followed by calcination of cobalt nitrate precursor in a flow of NO/He [5,6]. This method yielded a surfaceweighted cobalt particle size of *5 nm with a narrow particle size distribution.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…24, 29 We have previously reported that agglomeration of cobalt and nickel nitrate can effectively be prevented by replacing traditional air calcination with thermal treatment in 1% (v/v) NO/He flow, resulting in high NiO and Co 3 O 4 dispersions. 30,31 For silicasupported copper nitrate, it was reported that the drying step is of vital importance to the particle size distribution. 5 Drying at elevated temperatures resulted in agglomeration during the hydrolysis of copper nitrate hydrate to copper hydroxynitrate.…”
Section: ' Introductionmentioning
confidence: 99%
“…metals and supports used, the size of the supporting particles, dispersion of the active metal on the surface of the support [10,11,12]. The selectivity is related to the properties of the catalyst used but also to a high degree dependent of process parameters used like pressure, temperature, gas composition and gas flow.…”
Section: Introductionmentioning
confidence: 99%